Beyond Income Poverty : Nonmonetary Dimensions of Poverty in Uganda - Etang, Alvin (World Bank, Washington, DC, 2017)
The proportion of Ugandan households living in poverty reduced by more than half between 1993 and 2013. Using household survey data, this paper analyzes nonmonetary dimensions of poverty in Uganda for levels and trends, to explore whether the observed reduction in monetary-based poverty are reflected in the nonmonetary indicators of poverty. The results show that Uganda's progress in reducing poverty is strongly reflected in several nonmonetary indicators of poverty. The analysis finds that the trends in many nonmonetary indicators are consistent with the trend of monetary-based measure of poverty. The paper also examines whether progress has been as fast as would be expected, given Uganda's impressive performance in reducing poverty. Overall, the evidence indicates that progress on nonmonetary poverty was consistent with expectations, and faster than what would be expected, for some indicators, based on other countries' experiences. This finding is similar to Uganda's progress on reducing monetary poverty, which is also at the expected level based on experience in other countries.